2020
DOI: 10.1038/s41416-020-01189-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative, but not preoperative, inflammation-based prognostic markers are prognostic factors in stage III colorectal cancer patients

Abstract: Background Recent evidence suggests that both preoperative and postoperative inflammation-based prognostic markers are useful for predicting the survival of colorectal cancer (CRC) patients. However, associations between longitudinal changes in inflammation-based prognostic markers and prognosis are controversial. Methods The subjects of this study were 568 patients with stage III CRC between 2008 and 2014. Preoperative and postoperative neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…Most of the papers evaluated “preoperative NLR”, while some assessed NLR in a different way. Yasui et al stratified 568 CRC patients into three groups depending on inflammation status: preoperatively low (normal group), preoperatively high but postoperatively low (normalized group), and persistently high (elevated group) [ 52 ]. They indicated that the normal group showed a better prognosis than the elevated group regarding several inflammation-related markers, including NLR.…”
Section: Neutrophil-related Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the papers evaluated “preoperative NLR”, while some assessed NLR in a different way. Yasui et al stratified 568 CRC patients into three groups depending on inflammation status: preoperatively low (normal group), preoperatively high but postoperatively low (normalized group), and persistently high (elevated group) [ 52 ]. They indicated that the normal group showed a better prognosis than the elevated group regarding several inflammation-related markers, including NLR.…”
Section: Neutrophil-related Markersmentioning
confidence: 99%
“…Most of the studies about CRP-related makers adopted preoperative parameters. However, as mentioned above, Yasui et al analyzed the inflammation status between before and after surgery, and showed that postoperative, but not preoperative, inflammation-based markers (i.e., CAR, LCR, and NLR) were significantly associated with OS and RFS [ 52 ]. The best timing for the evaluation of CRP-related markers remains to be elucidated.…”
Section: Crp-related Markersmentioning
confidence: 99%
“…10 However, another study by Yasui and colleagues reported that the persistently low NLR group and exacerbation group (preoperative low to postoperative high NLR) showed no difference in survival in patients with stage III CRC. 9 To the best of our knowledge, the prognostic impact of NLR-delta and NLR-trend has been investigated in a limited manner. Cui et al analyzed both NLR-delta and…”
Section: Discussionmentioning
confidence: 99%
“…NLR-delta has been demonstrated as an alternative prognostic factor in patients with non-small cell lung cancer, hepatocellular carcinoma, gastric cancer, and anaplastic thyroid cancer. [11][12][13][14][15][16] However, there are still some discrepancies in the clinical significance of grouping the NLR-pre and NLP-post 9,10 and the clinical significance of NLR-delta in patients with CRC also showed conflicting results. 17,18 In addition, the significance of combining pre-and post-operative NLR (NLR-trend) and NLR-delta has rarely been evaluated simultaneously, and it remains unclear whether there is a difference in the strength of association with survival between the two dynamic matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Various systemic reviews and meta analyses have shown that postoperative mGPS has a strong prognostic value in the overall survival and recurrence-free survival of patients with colorectal cancer. [23][24][25] While effort is directed towards following systemic in ammation postoperatively, one particular study by Moyes et al correlates preoperative mGPS and white cell count to postoperative complications in patients undergoing curative resection for colorectal cancer, as shown in Tables 1 and 2 in their paper. 26 Systemic in ammation, besides concomitant sepsis and in ammatory pathology, is independently associated with cancer.…”
Section: Discussionmentioning
confidence: 99%